(untitled) (Research, Society and Development, 2021)
The objective was to describe and relate compounds from Cerrado plants with inhibitory action against pathogenic microorganisms for humans and animals. Therefore, a preliminary search was carried out in the Health Sciences Descriptors (DeCS) to define the words to be used in the literature survey. It defined as key words, “Antimicrobial or Bactericide or Fungicide” and “Plant or Vegetal” and “Cerrado or Cerrado Biome”. Through the Medical Subject Headings (MeSH) tool, it selected studies in which the combination of keywords were identified in the titles and/or abstracts of the studies. The search for articles was performed in the Science Direct, Web of Science and PubMed databases. Initially 48 studies were revealed, after reading in full were included for analysis, 10 articles published between the years (2017-2021). After evaluating the studies, 13 plant species belonging to 8 botanical families with antimicrobial potential were identified, with Fabaceae being the family with the highest number of species. For the extraction of compounds, plant leaves were the most used organ and ethanol, as a solvent. The major bioactive plant compounds were terpenes and phenolic compounds. The secondary metabolites detected in plant extracts showed different forms of action for microbial inhibition, under different concentrations. Plant compounds from the Cerrado are promising as alternatives to conventional antimicrobials, being important for the production of new drugs. The studies analyzed demonstrated that there are plant species native to the Cerrado that have already been studied with notorious antimicrobial potential.